2014
DOI: 10.1603/en13278
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maturity and Variety of Potato Plants on Oviposition and Probing ofBactericera cockerelli(Hemiptera: Triozidae)

Abstract: The ecological theory on host plant choice by herbivores suggests that mothers should choose plants that will maximize their offspring's success. In annual host plants, physiology (and therefore host suitability) is sometimes influenced by maturity and growth stage, which may influence female choice. Potato plants were grown under greenhouse conditions and used in choice and no-choice bioassays to determine the effect of plant maturity and variety on oviposition and number of stylet sheaths (which approximate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
1
3
1
Order By: Relevance
“…This may eventually result in infestation of the entire field. Regarding plant resistance to the potato psyllid, both antibiosis and antixenosis have been reported in potatoes (Butler et al, 2011;Diaz-Montano et al, 2014;Prager et al, 2014). However, the presence of these resistance mechanisms cannot be demonstrated in the present study.…”
Section: Resultscontrasting
confidence: 53%
“…This may eventually result in infestation of the entire field. Regarding plant resistance to the potato psyllid, both antibiosis and antixenosis have been reported in potatoes (Butler et al, 2011;Diaz-Montano et al, 2014;Prager et al, 2014). However, the presence of these resistance mechanisms cannot be demonstrated in the present study.…”
Section: Resultscontrasting
confidence: 53%
“…Likewise, Horton and Krysan (1990) assessed the probing and oviposition behaviours of Cacopsylla pyricula (Förster) (Hemiptera: Cicadellidae) and observed little correspondence between the percent of psyllids probing on different plant species and the percent of psyllids engaged in preoviposition activity. Similar findings were reported by Prager et al (2014a), who observed a lack of association between the number of eggs laid and the number of stylet sheaths of Bactericera cockerelli in potato plants.…”
Section: Relationship Between Stylet Sheath and Egg Countssupporting
confidence: 90%
“…In polyphagous insects, we can additionally examine aspects associated to the acceptance and/or rejection of plant species and what sets the limit of such differences between them. Often, these matters are addressed and treated as either a practical problem, in which case the plants of interest are generally domesticated plant species, typically referred to as "crops" (Romero et al 2019, Prager et al 2014a, or as an ecological question, in which case the plant-insect pairing may not involve any domesticated plant species at all. However, domesticated plant species are often bred for traits other than insect resistance, while wild plant species may have been under severe selection leading to the evolution of traits that protect them from herbivory (Whitehead et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Antixenosis resistance to ZC in some potato genotypes has been demonstrated (10). Later studies further inferred potential ZC resistance through antixenosis by quantifying differences in oviposition, feeding, and probing behavior (42,97). The breeding clone family A07781, with Solanum chacoense in its ancestry (US Department of Agriculture Agricultural Research Service, Small Grains and Potato Germplasm Research, Aberdeen, ID), has emerged as a promising candidate for future incorporation into commercial cultivars (42).…”
Section: Host Plant Resistancementioning
confidence: 99%